Ethnomathematics: Optimization of Students' Mathematical Reasoning Through the Traditional Ceremony of Seren Taun and The Banten Bendrong Lesung Dance - Kusuma, Jaka Wijaya; Caesarani, Sarah; Gustiana, Gita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The fundamental problem that causes this study is that the low mathematical reasoning ability of students and culture in Banten has not been explored optimally for classroom learning. This study aims to compare the mathematical reasoning ability of students who use ethnomathematics-based learning with conventional learning, as well as mathematical elements contained in Banten culture. The target is junior high school students with transformation materials. The approach used by the researcher is quantitative research. The research method used is a quasi-experiment with a pre-post control group design. The population in this study is grade IX students of SMP PGRI 1 Tangerang with a sample of 72 students. Researchers used independent sample t-tests to analyze the data. The results obtained by the researcher were the average post-test score of the experimental class of 72.56 and the control class of 54.11, which means that ethnomathematics-based learning is better than conventional learning in optimizing students' mathematical reasoning skills. Creativity is needed to find the elements of mathematics contained in Banten culture, and then it is necessary to conduct further research whether ethnomathematics-based learning can improve students' abilities other than reasoning.